European Unions: Labor's Quest for a Transnational Democracy - Croucher, Richard (Relations industrielles / Industrial Relations, 2009)
The article reviews the book, "European Unions: Labor's Quest for a Transnational Democracy," by Roland Erne.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; LABOR market; Labor Unions; Political behavior; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z